Design of Targeted Flurbiprofen Biomimetic Nanoparticles for Management of Arthritis: In Vitro and In Vivo Appraisal - Hagar I. Mohamed; Amal H. El-Kamel; Ghada O. Hammad; Lamia A. Heikal (MDPI AG, 2022)
Flurbiprofen (FLUR) is a potent non-steroidal anti-inflammatory drug used for the management of arthritis. Unfortunately, its therapeutic effect is limited by its rapid clearance from the joints following intra-articular injection. To improve its therapeutic efficacy, hyaluronic acid-coated bovine serum albumin nanoparticles (HA-BSA NPs) were formulated and loaded with FLUR to achieve active drug targeting. NPs were prepared by a modified nano-emulsification technique and their HA coating was proven via turbidimetric assay. Physicochemical characterization of the selected HA-BSA NPs revealed entrapment efficiency of 90.12 ± 1.06%, particle size of 257.12 ± 2.54 nm, PDI of 0.25 ± 0.01, and zeta potential of −48 ± 3 mv. The selected formulation showed in-vitro extended-release profile up to 6 days. In-vivo studies on adjuvant-induced arthritis rat model exhibited a significant reduction in joint swelling after intra-articular administration of FLUR-loaded HA-BSA NPs. Additionally, there was a significant reduction in CRP level in blood as well as TNF-α, and IL-6 levels in serum and joint tissues. Immunohistochemical study indicated a significant decrease in iNOS level in joint tissues. Histopathological analysis confirmed the safety of FLUR-loaded HA-BSA NPs. Thus, our results reveal that FLUR loaded HA-BSA NPs have a promising therapeutic effect in the management of arthritis.